Comparative metabolomic profiling of Cupriavidus necator B-4383 revealed production of cupriachelin siderophores, one with activity against Cryptococcus neoformans - Ahmed, Mohammed M. A.; Tripathi, Siddarth K.; Boudreau, Paul D. (Frontiers in Chemistry, 2023)
Cupriavidus necator H16 is known to be a rich source of linear lipopeptide siderophores when grown under iron-depleted conditions; prior literature termed these compounds the cupriachelins. These small molecules bear β-hydroxyaspartate moieties which contribute to a photoreduction of iron when bound as ferric cupriachelin. Here, we present the structural assignment of the cupriachelins from C. necator B-4383 grown under iron limitation. The characterization of the B-4383 cupriachelins is based on MS/MS fragmentation analysis which was confirmed with 1D- and 2D-NMR for the most abundant analogue (1). The cupriachelin congeners distinguish these two strains with differences in the preferred lipid tail, but our rigorous metabolomic investigation also revealed minor analogues with changes in the peptide core that hint at a potential mechanism by which these siderophores may reduce biologically unavailable ferric iron (4-6). Antifungal screening of the C. necator B-4383 supernatant extract and the isolated cupriachelin analogue (1) displayed inhibitory activity against Cryptococcus neoformans with IC50 values of 16.6 and 3.2 μg/mL, respectively. This antifungal activity could be explained by the critical role of the iron acquisition pathway in the growth and pathogenesis of the C. neoformans fungal pathogen.